2021
DOI: 10.2147/ccid.s289716
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Options for the Management of Itch in Atopic Dermatitis

Abstract: Pruritus is the most burdensome and prevalent symptom in patients suffering from atopic dermatitis. Treating atopic itch has historically been a challenge due to multiple underlying mechanisms within its pathogenesis and an incomplete understanding of them. In recent years, our understanding of these mechanisms have increased tremendously and subsequently, new treatments have reached the market that target the pathophysiology of atopic itch from different angles. In addition, there are several promising new tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Atopic dermatitis (AD) is a chronic inflammatory skin disease, which is characterized by relapsing eczematous, oozing and weeping pruritic symptoms over dry skin with epidermal hyperplasia ( 1 ). AD affects individuals worldwide, especially children, with increased prevalence in the last few decades ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic inflammatory skin disease, which is characterized by relapsing eczematous, oozing and weeping pruritic symptoms over dry skin with epidermal hyperplasia ( 1 ). AD affects individuals worldwide, especially children, with increased prevalence in the last few decades ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The management of AD with a focus on psychological stress includes autogenic training (AT) and progressive muscle relaxation (PMR) as relaxation methods; additionally, acupuncture has been reported to be effective as well [ 6 ] 7 . Studies of the musculoskeletal system have also demonstrated that high levels of psychological stress can modulate the autonomic nervous system and induce increased muscle tension, especially neck stiffness [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis is the most common inflammatory skin disease, characterized by impaired barrier function 69 . Current pharmacological management strategies include topical agents such as corticosteroids, calcineurin inhibitors and phosphodiesterase‐4 inhibitors, and systemic agents including broad‐spectrum immunosuppressants, cyclosporine, methotrexate, mycophenolate mofetil, and azathioprine 70 . While BTK inhibition is one of a number of therapeutic strategies under investigation, 71 recent additions to the armamentarium include monoclonal antibodies (dupilumab and tralokinumab), along with Janus kinase inhibitors (baricitinib, upadacitinib and abrocitinib) 72…”
Section: Btk Pathway Inhibition In the Treatment Of Skin Diseasesmentioning
confidence: 99%
“…69 Current pharmacological management strategies include topical agents such as corticosteroids, calcineurin inhibitors and phosphodiesterase-4 inhibitors, and systemic agents including broad-spectrum immunosuppressants, cyclosporine, methotrexate, mycophenolate mofetil, and azathioprine. 70 While BTK inhibition is one of a number of therapeutic strategies under investigation, 71 recent additions to the armamentarium include monoclonal antibodies (dupilumab and tralokinumab), along with Janus kinase inhibitors (baricitinib, upadacitinib and abrocitinib). 72 The penetration of antigens through the impaired dermatological barrier leads to production of cytokines such as thymic stromal lymphopoietin, which triggers BTK-dependent signaling and this may be of therapeutic interest.…”
Section: (B) Pemphigus: Dendritic Cells Presenting Desmoglein (Dsg) A...mentioning
confidence: 99%